The influence of sleep duration on patients with coronary artery disease: a four-year observational study - Ma, Runfeng; Wang, Ruoyu; Wang, Bingqian; Tang, Zihan; Qiu, Tian; Lu, Yiduo; Liu, Gang (Frontiers in Endocrinology, 2025)
BackgroundCoronary artery disease (CAD) is highly prevalent and fatal worldwide. In China, particularly in the southwest region, the association between CAD and sleep duration remains insufficiently understood. This study aims to investigate outcomes among CAD patients with varying sleep duration.MethodsIn a Southwest Chinese cohort, patients with CAD were categorized into three sleep duration groups: <6 hours, 6–8 hours, and >8 hours. Over a four-year follow-up, the endpoint including new-onset myocardial infarction and CAD-related deaths was recorded. The Fine-Gray model was employed to evaluate the estimated marginal occurrence probability of the target event. Additionally, Kaplan-Meier estimation and Cox regression analysis were conducted to further investigate the association between sleep duration and outcomes.ResultsThe study enrolled 816 residents with CAD, who had an average age of 69.2 ± 8.3 years old, of whom 40.2% were male. Across the three sleep duration groups (6-8h, <6h, and >8h), the hazard ratios (HRs) with 95% confidence interval for new-onset myocardial infarction were: 1.00 (reference), 2.67 (1.57-4.55) (P < 0.001), and 0.98 (0.30-3.21) (P=0.970). For CAD-related mortality, the HRs were: 1.00 (reference), 5.20 (2.53-10.68) (P < 0.001), and 5.02 (1.59-15.80) (P=0.006). This trend was consistently observed in both the Fine-Gray model and subgroup analyses.ConclusionsBoth short (<6 hours/day) and long (>8 hours/day) sleep duration were linked to an elevated risk of cardiac mortality among CAD patients in Southwest China. Short sleep duration was also found to be associated with high myocardial infarction risk.